Toxicity assessment of industrial engineered and airborne process-generated nanoparticles in a 3D human airway epithelial in vitro model - Bessa, Maria João (2022)
The advanced ceramic technology has been pointed out as a potentially relevant case of occupational exposure to nanoparticles (NP). Not only when nanoscale powders are being used for production, but also in the high-temperature processing of ceramic materials there is also a high potential for NP release into the workplace environment. In vitro toxicity of engineered NP (ENP) [antimony tin oxide (Sb2O3•SnO2; ATO); zirconium oxide (ZrO2)], as well as process-generated NP (PGNP), and fine particles (PGFP), was assessed in MucilAir™ cultures at air-liquid interface (ALI). Cultures were exposed during three consecutive days to varying doses of the aerosolized NP. General cytotoxicity [lactate dehydrogenase (LDH) release, WST-1 metabolization], (oxidative) DNA damage, and the levels of pro-inflammatory mediators (IL-8 and MCP-1) were assessed. Data revealed that ENP (5.56 µg ATO/cm2 and 10.98 µg ZrO2/cm2) only caused mild cytotoxicity at early timepoints (24 h), whereas cells seemed to recover quickly since no significant changes in cytotoxicity were observed at late timepoints (72 h). No meaningful effects of the ENP were observed regarding DNA damage and cytokine levels. PGFP affected cell viability at dose levels as low as ∼9 µg/cm2, which was not seen for PGNP. However, exposure to PGNP (∼4.5 µg/cm2) caused an increase in oxidative DNA damage. These results indicated that PGFP and PGNP exhibit higher toxicity potential than ENP in mass per area unit. However, the presence of a mucociliary apparatus, as it occurs in vivo as a defense mechanism, seems to considerably attenuate the observed toxic effects. Our findings highlight the potential hazard associated with exposure to incidental NP in industrial settings.